Case Report: Efficacy, safety, and favorable long-term outcome of early treatment with IL-1 inhibitors in a patient with chronic infantile neurological cutaneous articular (CINCA) syndrome caused by NLRP3 mosaicism - Costagliola, Giorgio; D’Elios, Sofia; Cappelli, Susanna; Massei, Francesco; Maestrini, Giulia; Beni, Alessandra; Peroni, Diego; Consolini, Rita (Frontiers in Pediatrics, 2024)
Chronic infantile neurological cutaneous articular (CINCA) syndrome is an autoinflammatory disease encompassed in the group of cryopyrin-associated periodic syndromes (CAPS). Patients suffering from CINCA have a high risk of developing chronic sequelae, including deforming arthropathy, chronic meningitis, neurodevelopmental delay, neurosensorial hearing loss, and others.The diagnosis of CINCA presents several difficulties, as the clinical phenotype could be difficult to recognize, and almost half of the patients have negative genetic testing. In this paper, we describe the case of a patient presenting with the typical phenotype of neonatal-onset CINCA and who resulted negative for NLRP3 mutations. Based on the clinical judgment, the patient underwent treatment with anti-interleukin-1 (IL-1) agents (anakinra and, later, canakinumab) resulting in a complete clinical and laboratory response, that allowed to confirm the diagnosis. Additional genetic investigations performed after the introduction of anti-IL-1 therapy allowed to evidence a pathogenic mosaicism in the NLRP3 gene. After a 12-year follow-up, the patient has not experienced chronic complications. Although genetics is rapidly progressing, this case highlights the importance of early diagnosis of CINCA patients, in order to start the appropriate anti-cytokine treatment even in the absence of a genetic confirmation, when the clinical and laboratory picture is highly suggestive.